1875 Va. Acts 102, ch. 124 - (:unkn) unknown (My University, 1875)
Prohibited the carry of any gun, pistol, Bowie knife, dagger, or other dangerous weapon into places of public worship without sufficient cause.
Keywords: CARRY - CERTAIN PUBLIC PLACES